Efektivitas Pendistribusian Dana Zakat dalam Program Jatim Makmur Untuk Meningkatkan Ekonomi Mustahik Studi Kasus di Baznas Provinsi Jawa Timur - Qurrotul Uyun (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze and measure the mechanism of zakat fund distribution within the Jatim Makmur Program and the effectiveness of zakat fund distribution in the Jatim Makmur Program for improving the economy of mustahik (recipients) in East Java Province. The research utilizes a qualitative method with a case study approach, focusing the research location within the working area of BAZNAS (National Amil Zakat Agency) East Java Province. Data were collected through observation, interviews, and documentation. The results show that the distribution of zakat funds through the Jatim Makmur Program has been effective overall in the indicators of targeting accuracy and program objectives. However, the indicators for program socialization and program monitoring or supervision were assessed as effective but not yet optimal. In the distribution mechanism, the majority of assistance is channeled in non-cash forms (such as business equipment and raw materials) to avoid the misuse of funds, such as for paying off debts to loan sharks . Nevertheless, the program also demonstrates flexibility by distributing cash assistance or interest-free loans for certain specific cases..